Cyanidin attenuates Aβ25-35-induced neuroinflammation by suppressing NF-κB activity downstream of TLR4/NOX4 in human neuroblastoma cells - Sarinthorn Thummayot (2018)
© 2018, Shanghai Institute of Materia Medica, CAS and Chinese Pharmacological Society. All rights reserved. Cyanidin is polyphenolic pigment found in plants. We have previously demonstrated that cyanidin protects nerve cells against Aβ25-35-induced toxicity by decreasing oxidative stress and attenuating apoptosis mediated by both the mitochondrial apoptotic pathway and the ER stress pathway. To further elucidate the molecular mechanisms underlying the neuroprotective effects of cyanidin, we investigated the effects of cyanidin on neuroinflammation mediated by the TLR4/NOX4 pathway in Aβ25-35-treated human neuroblastoma cell line (SK-N-SH). SK-N-SH cells were exposed to Aβ25-35(10 μmol/L) for 24 h. Pretreatment with cyanidin (20 μmol/L) or NAC (20 μmol/L) strongly inhibited the NF-κB signaling pathway in the cells evidenced by suppressing the degradation of IκBα, translocation of the p65 subunit of NF-κB from the cytoplasm to the nucleus, and thereby reducing the expression of iNOS protein and the production of NO. Furthermore, pretreatment with cyanidin greatly promoted the translocation of the Nrf2 protein from the cytoplasm to the nucleus; upregulating cytoprotective enzymes, including HO-1, NQO-1 and GCLC; and increased the activity of SOD enzymes. Pretreatment with cyanidin also decreased the expression of TLR4, directly improved intracellular ROS levels and regulated the activity of inflammation-related downstream pathways including NO production and SOD activity through TLR4/NOX4 signaling. These results demonstrate that TLR4 is a primary receptor in SK-N-SH cells, by which Aβ25-35triggers neuroinflammation, and cyanidin attenuates Aβ-induced inflammation and ROS production mediated by the TLR4/NOX4 pathway, suggesting that inhibition of TLR4 by cyanidin could be beneficial in preventing neuronal cell death in the process of Alzheimer's disease.